Acoustic Instruments for the Study of the Reaction of Fishes - Sivadas, T. K. (Fishery Technology, 1970)
There are many improvised methods practised at present for attracting fishes by sound. Fishermen produce sounds by beating on the body of dugout canoes and catamarans for scaring fishes. In inland fisheries a metal bell is sometimes used over water for producing sound. All these methods are much inconvenient and inefficient. Moreover the particular frequency and type of sound to which the species of fishes are to be attracted, have to be determined after detailed study for obtaining the best results. According to the results obtained from the works done in U. S. S. R. and Japan, the sound audible to fishes is almost the same as that to the human beings, ie; from 30 Hz to 10000 Hz. Two instruments are described in this communication developed for the study of the reaction of fishes towards sound. The electrical instrument produces intense sound of a fixed frequency under water while the electronic one produces slightly less intense sound of continuously variable frequency from 100 Hz to 8000 Hz. The intensity of sound also can be varied continuously from zero to maximum, in the latter instrument.